The Science (or Nonscience) of Research Into Sudden Infant Death Syndrome (SIDS) - Goldwater, Paul Nathan (Frontiers in Pediatrics, 2022)
This Viewpoint paper presents a timely and constructive critique of mainstream SIDS research. It is concerning that 21st-century medical science has not provided an answer to the tragic enigma of SIDS. The paper helps explain why this is so and illustrates possible shortcomings in the investigation of Sudden Infant Death Syndrome/Sudden Unexplained Infant Death (SIDS/SUID) by mainstream researchers. Mainstream findings are often based on questionable and dogmatic assumptions that return to founding notions such as the Triple Risk Hypothesis and the contention that the mechanisms underlying SIDS/SUID are heterogeneous in nature. The paper illustrates how the pathological findings in SIDS have been under-investigated (or ignored) and that key epidemiological risk factors have slipped from memory. This apparent amnesia has resulted in failure to use these established SIDS facts to substantiate the significance of various neuropathological, neurochemical, or other research findings. These unsupported findings and their derivative hypotheses are therefore ill-founded and lack scientific rigor. Conclusion: The deficits of SIDS “science” revealed in this paper explain why the SIDS enigma has not yet been solved. To make progress in understanding SIDS, it is important that researchers, as scientists, uphold the standards of research. Encouragement for new directions of research is offered.